Determining stress management activities for various Myers-Briggs personality types. - Ghidella, J. (The Young Researcher)
Stress, a component of everyday life, can be detrimental to health. Previous research has shown an increase in studies on stress in recent years, but little on linking stress and personality type. Because of this, new and innovative research in stress management is of utmost importance. This study combined the personality type theory of Myers-Briggs with de-stressing activities to determine which personality types found which de-stressing activities the most effective. The study focused on teenagers to bring more light to their stress management. There were different correlations, but they were insignificant. A conclusive statement cannot be made about the original research question, but a plethora of useful information was still discovered. While the results were varied, the conclusion of this study was that it was possible to determine which activities would most benefit people with certain personality types.